If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
3*x-(6/y) = 9 // - 9
3*x-(6/y)-9 = 0
3*x-6*y^-1-9 = 0
3*x-6*y^-1-9 = 0 // + -6*y^-1-9
3*x = -(-6*y^-1-9) // : 3
x = (-(-6*y^-1-9))/3
x = (9-(-6*y^-1))/3
x = (9-(-6*y^-1))/3
| 0.04x^2+-0.8x+22=0 | | 8x(-x+9)=0 | | 0.04x^2+-0.8x=0 | | f(x)=0.04x^2-0.8x | | 1/3x1/16 | | 40=x(x-6) | | (6c^2+2c-8)-(8c^2+c-13)= | | 11(z+1)-4(z-4)=4(z-4)+2(z-4) | | Y=30In(X+4) | | (2-y)(5y+4)=0 | | (6t-5)=2(t+1)+4 | | -3p+8=6-(10p+2) | | .13(X+50)=24.9 | | 100x+20x^2=0 | | y=sin(tan(7x)) | | 22x+13=18x+13 | | 9x^2+12h+4=0 | | K=10ys | | 6(2t-3)+5=36-t | | 22x+13x=18x+13 | | 2(x+15)=-x+30 | | 0.85x+0.05(20-x)=0.10(26) | | 7ln(x+3)-5ln(x)= | | x^3+2x^2-3x=-6 | | .5(x-500000)=10 | | 28x^2+1x-45= | | 5y=x-4 | | Ln(x+9)+ln(x-9)=o | | 11+2x=-3(x-1)+3x | | w=12+24 | | 2(b+2)-(9+b)=-4 | | -4x-6=-2x-2 |